ISM Properties of a Massive Dusty Star-forming Galaxy Discovered at z similar to 7 - Strandet, M. L.; Weiss, A.; De Breuck, C.; Marrone, D. P.; Vieira, J. D.; Aravena, M.; Ashby, M. L. N.; Bethermin, M.; Bothwell, M. S.; Bradford, C. M.; Carlstrom, J. E.; Chapman, S. C.; et al. (IOP PUBLISHING LTD, 2017)
We report the discovery and constrain the physical conditions of the interstellar medium of the highest-redshift millimeter-selected dusty star-forming galaxy to date, SPT-S J031132-5823.4 (hereafter SPT0311-58), at z = 6.900 +/- 0.002. SPT0311-58 was discovered via its 1.4 mm thermal dust continuum emission in the South Pole Telescope (SPT)-SZ survey. The spectroscopic redshift was determined through an Atacama Large Millimeter/submillimeter Array 3 mm frequency scan that detected CO(6-5), CO(7-6), and [C I](2-1), and subsequently was confirmed by detections of CO(3-2) with the Australia Telescope Compact Array and[C II] with APEX. We constrain the properties of the ISM in SPT0311-58 with a radiative transfer analysis of the dust continuum photometry and the CO and [C I] line emission. This allows us to determine the gas content without ad hoc assumptions about gas mass scaling factors. SPT0311-58 is extremely massive, with an intrinsic gas mass of M-gas = 3.3 +/- 1.9 x 10(11) M-circle dot. Its large mass and intense star formation is very rare for a source well into the epoch of reionization.